Learning in a digital world: an introduction - Diaz, Paloma; Ioannou, Andri (My University, 2019)
In recent years, several scholars have called for more inquiry on the role of interactive media in learning in the digital and hyperconnected world. While the interplay of technology and learning may be difficult to fully unfold, current evidence suggests that technological innovations have an important effect on learning, engagement, and achievement in all educational settings—formal, non-formal, and informal. This book compiles contemporary and multidisciplinary research in this area, with the goal of arousing other investigators to contribute to the growing empirical literature on interactive media for learning. The chapters in this book explore research questions on technologically mediated learning from a variety of theoretical and methodological frameworks in several different types of educational contexts, and from different participant perspectives (students and teachers). In doing so, the book is expected to shed light and raise academic discussions on the interplay of interactive media and learning in formal, non-formal, and informal educational settings—how learning gains emerge and are documented, and how the use of interactive media relates to important behavioral, motivational, and achievement outcomes.
Keywords: Learning; Education; Interactive media; Educational technology; Technology-Enhanced learning; Emerging technologies; ICT; Formal; Non-formal; Informal